Factors Associated With the Need for Pharmacological Management of Neonatal Opioid Withdrawal Syndrome. (October 2020) - Scott, Lisa Fath; Guilfoy, Veronica; Duwve, Joan M.; Rawl, Susan M.
Abstract : Background: Neonatal opioid withdrawal syndrome (NOWS) is a significant and growing health problem that affects more than 23, 000 infants annually, with an estimated hospital cost of more than $720 million. Purpose: The purpose of this study was to examine factors associated with the need to initiate medication for the treatment of NOWS. Methods: A retrospective review of medical records was conducted of 204 infants born to mothers who used opioids during pregnancy from April 2011 to September 2017. Associations between maternal, infant, and environmental factors and the need for neonatal pharmacological management were examined using χ 2, t tests, and regression analysis. Results: Of 204 neonates exposed to opioids prenatally, 121 (59%) developed symptoms of NOWS, requiring treatment with morphine. Neonates requiring morphine had significantly higher gestational ages (37.7 weeks vs 36.4 weeks; P < .001), and mothers were present at the neonate's bedside for a lower proportion of their total hospital stay (57% vs 74% of days; P < .001). Maternal factors associated with the need for neonatal medication treatment included the mother's reason for opioid use ( P = .014), primary type of opioid used ( P < .001), tobacco use ( P = .023), and use of benzodiazepines ( P = .003). Implications for Practice: This research provides information regarding the proportion of infants exposed to opioids prenatally who develop NOWS that requires treatment, as well as maternal, infant, and environmental factors associated with the need for neonatal medication use. Implications for Research: Future research is needed to examine these relationships prospectively in a larger and more diverse sample.